Demographic analysis of turnover intentions amongst Nigerian high school teachers - Ajayi, S.; Olatunji, Oluwole (Society for the Provision of Education for Rural Australia, 2017)
Nigeria’s Universal Basic Education program massifies access to education. School enrolment numbers have risen consistently. However, pre-existing issues have often diminished the incentive to achieve the greater goals of massification efforts. This study investigates teachers’ intentions to quit; to wit, the relationship between turnover causations and teachers’ demographic variables [including age, sex, work status, qualifications and years of experience]. We analysed a total of 925 questionnaires received from public high school teachers in Ogun State, south-western Nigeria. Data were grouped for analysis by respondents’ gender, age, qualifications, work status and years of experience. The frameworks for the analysis were: job satisfaction, personal health, work-social life balance, involuntary turnover, workload stress, LEAP leadership behaviour, organizational commitment, work environment and motivation. Methods used for analyses include descriptive methods, analysis of variance, pairwise comparisons, Cronbach’s Alpha reliability estimation and T-test statistics. The study found significant correlation between teachers’ intention to quit, and teachers’ age, qualification, work status and experience. Teachers aged 36 – 45 years are least willing to quit. Teachers aged 55 years and above, and those aged below 35 years are most willing to quit. The managerial insight to this is that managers need to target employees within the age brackets that are most willing to stay-on, and to work out appropriate strategies to retain those who are most valuable to the goals of the UBE and the organizations in which they serve.